ALGORITMA NON-PHOTOREALISTIC RENDERING UNTUK KARTUN MENGGUNAKAN K-MEANS DAN CANNY - Budiman Baso; Irit Maulana Sapta; Saniyatul Mawaddah (Department of Information Technology, Universitas Timor, Indonesia, 2021)
Cartoons are one type of illustration usually in a non-realistic or semi-realistic style. To make a cartoon drawing manually requires good drawing ability. So, not everyone can make cartoons. This research proposes a non-photorealistic rendering algorithm to create cartoon drawings automatically. The algorithm consists of four phases. First, create an image abstraction using bilateral filtering. Second, using kmeans clustering for abstract image quantization. Third, get the contour lines of the drawing using the canny algorithm. Fourth, contour lines and quantized images are combined. The results show that this algorithm can produce good visualization of cartoon images.